2012
DOI: 10.1183/09031936.00119712
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal inflammation in COPD: a systematic review: Table 1–

Abstract: In this review, we demonstrate that patients with chronic obstructive pulmonary disease (COPD) frequently report sinonasal symptoms. Furthermore, we present evidence that smoking on its own can cause nasal disease and that, in COPD patients, nasal inflammation mimics that of the bronchi. All this evidence suggests that COPD-related sinonasal disease does exist and that smoking on its own rather than systemic inflammation triggers the condition. However, COPD-related sinonasal disease remains to be characterise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 57 publications
2
27
0
1
Order By: Relevance
“…Another potential explanation for these results is that smoking is associated with reversible sinonasal inflammation . Inflammation in the olfactory mucosa is associated with olfactory dysfunction, and treatment of this is associated with improvement .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential explanation for these results is that smoking is associated with reversible sinonasal inflammation . Inflammation in the olfactory mucosa is associated with olfactory dysfunction, and treatment of this is associated with improvement .…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for these results is that smoking is associated with reversible sinonasal inflammation. 38 Inflammation in the olfactory mucosa is associated with olfactory dysfunction, and treatment of this is associated with improvement. 39 Cessation of smoking may result in the resolution of acute or chronic inflammation, which would result in improved olfaction, consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that COPD patients often report sinonasal symptoms. However, recently, Håkansson et al in a systematic review of the literature suggest that, although the prevalence of rhinosinusitis symptoms is increased in patients with COPD, this association is ambiguous since smoking itself has several effects on the nasal mucosa. We have found that smoking is a confounding variable in the association between CPOD and rhinosinusitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal inflammation is present in healthy smokers and to a further extent in COPD patients, especially in those who continue to smoke . However, only a few studies with relatively small numbers of COPD patients assessed the frequency and impact of CNS on pulmonary symptoms and QoL A recent review underlined that more studies are needed to assess the impact of nasal symptoms on the QoL in COPD patients . Therefore, the present analyses were designed to investigate, in a series of well‐defined COPD patients, the prevalence of and risk factors for CNS, and their association with dyspnoea and QoL.…”
Section: Introductionmentioning
confidence: 99%